The effect of the Numbered Heads and Listening Triangle strategies on learning some basic volleyball skills among eighth-grade students - Yousef, Asst.Prof.Dr.Saadi Omar Yousef; Khaled, Nigerfan Mashkhti Khaled (Sulaimani Journal for Humanities, 2025)
This study aimed to explore: • The impact of the Numbered Heads Strategy and the Listening Triangle Strategy on learning specific basic volleyball skills. • A comparison of the effectiveness of the Numbered Heads Strategy versus the Listening Triangle Strategy in teaching these skills. To achieve these objectives, the researchers formulated the following hypotheses: 1. Significant differences exist between the pre-test and post-test mean scores of the two experimental groups in learning basic volleyball skills, favoring the post-test results. 2. No significant differences exist between the post-test mean scores of the two experimental groups in learning basic volleyball skills. The researchers adopted an experimental design featuring equivalent groups with pre-tests and post-tests. The study population consisted of 69 eighth-grade students from Sarsink, Amedi District, Duhok Governorate, during the 2024–2025 academic year. Students were distributed across two classes (A and B), and a sample of 28 students (14 from each class) was randomly selected using a simple lottery method. An assessment tool was developed to measure the skill performance of the experimental groups in volleyball. The educational curriculum for both experimental groups consisted of 8 instructional units, with one unit per week lasting 40 minutes. Upon completing the program, skill performance tests were conducted, video-recorded, and evaluated by specialists using structured scoring sheets. Statistical analysis was performed using SPSS software. Findings: • Both strategies effectively enhanced the acquisition of basic volleyball skills. • The Numbered Heads Strategy did not show superiority over the Listening Triangle Strategy in skill development. Recommendations: • Employing both strategies is recommended for teaching volleyball skills due to their proven effectiveness. • Training workshops should be organized to promote awareness and educate instructors on the practical implementation of modern learning strategies in teaching.
Keywords: Numbered Heads strategy; Listening Triangle strategy; Basic Volleyball Skills; High School Students